Comparative study of SNP density in genes associated with milk traits in mammals including livestock species - Avnish K. Bhatia; Aruna Pandey; Birham Prakash (Journal of Livestock Biodiversity, 2025)
Single Nucleotide polymorphisms (SNPs) are a common form of genetic diversity in organisms. SNPs are discovered throughout genomic sequence that warrants prioritization of selection of genomic regions rich in SNPs for efficient discovery and validation in laboratory experiments. Species like human, mouse, and cow have been extensively studied in the last decade and a large number of SNPs are available in online databases for these species. Assuming homology of the pattern of distribution of SNPs in genomes of various mammalian species, SNP rich genomic regions of extensively investigated species can be picked and the corresponding genomic regions in less studied species can be prioritized for SNP discovery. In the present study, 12 genes for milk traits in cow have been considered for comparative plotting of SNP density on homologous genomic regions in cow and five other mammalian species namely human, mouse, dog, horse and pig through multiple sequence alignment of genomic sequences. The bioinformatics analysis revealed conservation in SNP density in corresponding genomic regions of the investigated species providing targeted regions for increasing SNP discovery.